The Role of Context in Pragmatic Interpretation - Nazeeva Yusrina; Tazkiya Aulia Ibriza; Hikmah Lubis; Sakinah Azzahra; Deasy Yunita Siregar (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This research investigates the role of context in pragmatic interpretation, focusing on how context influences the understanding of meaning in communication. By examining various aspects such as implicature, deixis, presuppositions, and speech acts, the study highlights how speakers and listeners navigate meaning through contextual clues. The research employs a qualitative approach, gathering data from real-life interactions, including interviews and observations. Findings reveal that context is not just a passive backdrop but an active participant in shaping meaning, particularly in intercultural communication. This study emphasizes the dynamic nature of context and its indispensable role in pragmatic interpretation, offering insights for language teaching, intercultural communication, and artificial intelligence applications.